Leading a culture of learning - Harland, Jill (Routledge, 2021)
"This practical book is designed to help school leaders develop a sustainable culture of learning across the curriculum. It offers a personal insight into how one school embraced a range of dialogic and analytical tools to create an environment in which all stakeholders were inspired to evaluate and innovate. Each chapter tackles one piece of the 'jigsaw' that makes up a successful school environment, considering topics such as Attitudes for Learning, Coaching for learning and Love of Learning. Utilising theory, case studies and activities, it illustrates how the reader can realistically and practically increase student attainment in their own school setting. This book will help leaders: Develop a supportive and encouraging leadership style that will create a cycle of self-improvement and self-efficacy for all ; Adapt the curriculum to focus on progress and engagement ; Use the Philosophy 4 Children strategies to promote deeper thinking and enquiry, increasing the rate of school improvement through a system of enquiry based staff professional development Using an inner city primary school as a working example, this book will be a source of inspiration and encouragement for school leaders, teachers and school advisors looking to cultivate and embed a love of learning into their school"--
Keywords: Education; Educational attainment; Academic achievement; Mentoring in education